School social work an evidence-informed framework for practice - Kelly, Michael S. (Michael Stokely), 1968- (New York ; Oxford : Oxford University Press, 2010)
This text offers school social work students and veteran practitioners a framework for choosing their interventions based on the best evidence. It synthesizes the evidence-based practice process with recent conceptual frameworks of school social work clinical practice offered by leading scholars and policymakers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School social work -- United States